Factors influencing childhood immunisation in an urban area of Brazil. Issue 4 (August 1992) - Barreto, T V; Rodrigues, L C
Abstract : STUDY OBJECTIVE–The aim was to examine the factors associated with incomplete vaccination in an urban area in Sao Paulo, Brazil; and to explore whether differences in vaccine coverage in the catchment area of health centres remain after the demographic constitution of the population in these areas is controlled for. DESIGN–The children were selected as controls for a case-control study. 455 children were selected at random (but age matched) from the health centre registries. Data was collected from the health centre records and from home interviews. SETTING–All children were registered in FAISA, a municipal health service comprising a large network of health centres and hospitals. FAISA's services are free at the point of delivery, and over 85% of the city's children are registered. PARTICIPANTS–Participants were selected to represent, except in their age distribution, all children registered in the municipal health service. MEASUREMENTS AND MAIN RESULTS–Information was collected on subjects' vaccine history, year of birth, sex, birth order and birth weight, and health centre of registration; their mothers' age, education, and marital status; and the family's income per capita and history of migration. Analysis was undertaken to identify risk factors for vaccination and whether the differential coverage in health centres' catchment areas remained after demographic characteristics of the population were controlled for. The high coverage for DPT and polio vaccines suggests that low overall coverage was not simply a result of mothers failing to bring children for vaccination. The variable that best predicted vaccine coverage was year of birth. Children born to immigrant mothers or into large families had lower vaccine uptake. The characteristics of children and their mothers did not account for the variation in vaccination coverage in catchment areas of different health centres. CONCLUSIONS–It is likely that in this area vaccination completeness was associated mainly with the health centre's ability to deliver vaccination to the target population.